Mindfulness Training in Primary Schools Decreases Negative Affect and Increases Meta-Cognition in Children - Vickery, Charlotte E.; Dorjee, Dusana (Frontiers in Psychology, 2016)
Childhood well-being programmes offer an ‘early window’ of opportunity for children to develop emotion regulation capacities and foster positive psychological growth. Studies investigating the feasibility and impact of mindfulness programmes on emotional well-being when delivered by school teachers in pre-adolescence are scarce. We report findings from a controlled feasibility pilot assessing acceptability and emotional well-being outcomes of an eight-week mindfulness programme (Paws b) delivered by school teachers within a regular school curriculum. Emotional well-being was measured using self-report questionnaires at baseline, post-training and three month follow-up, and informant reports were collected at baseline and follow-up. Seventy one participants aged 7-9 years were recruited from three primary schools in the UK (training group n = 33; control group n = 38). Acceptability of the programme was high with 76% of children in the training group reporting ‘liking’ practicing mindfulness at school, with a strong link to wanting to continue practicing mindfulness at school (p < 0.001). Self-report comparisons revealed that relative to controls, the training group showed significant improvements in negative affect at follow-up, with a large effect size (p = 0.010, d = 0.84). Teacher reports (but not parental ratings) of meta-cognition also showed significant improvements at follow-up with a large effect size (p = 0.002, d = 1.08). Additionally, significant negative correlations were found between changes in mindfulness and emotion regulation scores from baseline to post-training (p = 0.038) and pre-training to follow-up (p = 0.033). Findings provide initial evidence that the Paws b programme in children aged 7-9 years can (a) be feasibly delivered by primary school teachers as part of the regular curriculum, (b) is acceptable to the majority of children, and (c) significantly decreases negative affect and may improve meta-cognition.